Alley-cropping stabilizes maize yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A long-term trial which compared maize crops with and without alley-cropping, and alley cropping with and without fertilizer, has been undertaken in Gandajika, Zaire. This has shown that although alley-cropping alone maintains soil productivity,...